PEMBENTUKAN KARAKTER TOKOH SONJA DALAM NOVEL KELAB DALAM SWALAYAN KARYA ABI ARDIANDA (TINJAUAN PSIKOLOGI SASTRA) - Agus Setiawan; Cutiana Windri Astuti; Karisma Dwi Widiana (Universitas Hamzanwadi, 2026)
This study aims to analyze the formation of Sonja's character in the novel Kelab Dalam Swalayan by Abi Ardianda through a review of literary psychology. The analysis in this study uses Skinner's behaviorism theory to determine the formation of Sonja's character. The method used is descriptive qualitative with reading techniques, note-taking techniques, and literature studies. These techniques include reading, listening, recording data, and analyzing quotes and dialogues in the novel. The results of the study show that the formation of Sonja's character is influenced by internal stimuli (family). External stimuli occur because the presence of Nohan (her future husband) changes Sonja's mindset and behavior in controlling past trauma. Second, character formation is influenced by responses to family stimuli. Sonja prefers to be silent because her mother has full control in the family. Meanwhile, responses to environmental stimuli in the form of the influence of others change behavior to become easily influenced. The results of this study can be used as teaching materials for literary learning related to character traits that are dynamic and influenced by various factors. In addition, it can be integrated with the learning of character values ​​in schools.